SISTEM INFORMASI PENDATAAN KARYAWAN GUDANG PADA PT. TEMPO BANDA ACEH DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN WEB-BASE - Fahkrurrazi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2020)
The warehouse employee information system is one of the data processing activities at PT. Tempo Banda Aceh, to get information about warehouse employees, it becomes more focused and easy to obtain. In writing this Final Project (TA), the author only discusses the problem of warehouse employees and data management mechanisms at PT. Tempo Banda Aceh and designed a warehouse employee data collection information system using PHP and MySQL. The purpose of writing is to understand the problems of warehouse employees and data management at PT. Tempo Banda Aceh and made a supporting application about warehouse employee information systems using PHP and MySQL. The data collection needed in writing this report was obtained by two methods, namely literature study related to literature, library books, and other scientific works, field studies by conducting interviews, and direct observation of objects related to this Final Project (TA). The warehouse employee information system is carried out by one of the administrative staff and assisted by 2 (two) warehouse employee administrative staff to record and input warehouse employee data. From the research results, it can be concluded that the warehouse employee information system at PT. Tempo Banda Aceh has followed the procedure and uses a computer with the PHP and MySQL language programs as its database.